PENINGKATAN KESEJAHTERAAN ANGGOTA ZIDAM III/ SILIWANGI MELALUI PENGUATAN KELEMBAGAAN KOPERASI KARTIKA YUDHA KARYA JAYA - Jaka Kartiwa (Comm-Edu (Community Education Journal), 2018)
This study aims to 1. To know the planning of Welfare Improvement Member ZIDAM III Siliwangi Through Institutional Strengthening Kartika Yudha Karya Jaya Cooperative. 2. To know the process of Welfare Improvement of ZIDAM III Siliwangi Members through Institutional Strengthening Kartika Yudha Karya Jaya Cooperative. 3. To know what factors are encouraging and inhibiting and the result of Welfare Improvement of ZIDAM III Siliwangi Members through Institutional Strengthening Kartika Yudha Karya Jaya Cooperative. This research uses descriptive qualitative research method, with data collection techniques through observation, interview, documentation and literature study The result of the research shows that improving the welfare of Cooperative Members ZIDAM III Siliwangi Through Institutional Strengthening Kartika Yuda Cooperative not only develop in the field of saving and lending services but also experienced in the field of photocopy business, staff canteen business, and others that aims to meet the needs in Zidam III Siliwangi agency. This cooperative provides a very big role in the welfare of its members, the cooperative as a place of human resource development training is to provide skills training to employees or members of Zidam III Siliwangi. Cooperative as a lender to members is to provide the required capital members. The driving factor is the increase of knowledge and skills, while the inhibiting factor is that the members/employees do not understand the rules related to the cooperative.